The consolation of philosophy - Boethius, -524 (Harvard University Press, 2008)
Composed while its author was imprisoned, this book remains one of Western literature's most eloquent meditations on the transitory nature of earthly belongings, and the superiority of things of the mind. Slavitt's translation captures the energy and passion of the original. And in an introduction intended for the general reader, Seth Lerer places Boethius's life and achievement in context.